The impacts of the Samarco mine tailing spill on the Rio Doce estuary, Eastern Brazil. Issue 1 (15th July 2017) - Gomes, Luiz Eduardo de Oliveira; Correa, Lucas Barreto; Sá, Fabian; Neto, Renato Rodrigues; Bernardino, Angelo Fraga
Abstract: Over 50 million cubic meters of mining tailings were released in the Rio Doce basin after the collapse of the Fundão dam (Samarco) in November 2015. Predicting significant impacts on the Rio Doce estuary, we sampled sediments to investigate short-term impacts on the benthic assemblages and trace metal accumulation on estuarine sediments. With the arrival of the tailing plumes in the estuary, we detected a predominance of clay particles and increased trace metal concentrations of up to 5 times in some areas. The rapid sedimentation after the impact also impacted estuarine macrofaunal assemblages through loss surface-dwelling taxa. As expected, the impacts on benthic assemblages observed up to 3 days after the arrival of tailings were not clearly associated with trace metal concentrations, but long-term effects need to be studied. We recommend that the high spatial variability within the estuary be considered in future impact assessment studies. Graphical abstract: Highlights: Mine tailings impacted the sediment quality in the Rio Doce estuary. Trace metal concentrations increased by 2 to 5 times after the impact. Benthic macrofauna diversity, composition and trophic groups were impacted. Future environmental assessments need strong sampling designs within the estuary.